The Properties of Salam Leaf Extract (Syzygium Polyanthum) with Different Solvent Ratio and Processing Time Using Ultrasonication-Assisted Extraction Method - Bima Putra Pratama; Yudi Pranoto; Supriyadi; Respati Tri Swasono (Journal of Applied Science and Engineering, 2022)
Salam leaf (Syzygium polyanthum) is an Indonesian traditional herbs with high bioactive compound potential. Unfortunately, as an alternative method that is friendly to heat-susceptible bioactive compound, the ultrasonication extraction method has not been widely used to extract Salam leaves. Meanwhile, the processing time and the ratio of the use of solvents are some of the determinants of the performance of this method. Hence, this research examined the ultrasonication method for extracting bioactive compounds from Salam leaf from the time and ratio of the solvent used. The results were showed that the best condition was from the solvent ratio to sample of 12:1 for 15 min extraction time. These conditions gave results in an 18.57% yield of salam leaf extract, 74.20 ± 0.19 mg Gallic acid equivalent/g salam leaf extract of total phenolic content, 22.00 ± 0.08 mg Quercetin equivalent/g salam leave extract of total flavonoid content, 78.79% of 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, and IC50 antioxidant activity of 20.25 µg/ml salam leave extract. The best extraction conditions are able to provide Salam leaf extract with very strong antioxidant potential.